The Influence of Managerial Competence, Innovation, and Market Orientation on the Performance of Micro, Small and Medium Enterprises (MSMEs) - Sudirjo, Frans; Zaini, Moh.; Rahmanto, Basuki Toto; Juminawati, Sri (West Science Journal Economic and Entrepreneurship, 2025)
This study investigates the impact of managerial competence, innovation, and market orientation on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Using a quantitative approach, data were collected from 220 MSMEs and analyzed through Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that all three constructs significantly and positively influence MSME performance, with managerial competence demonstrating the strongest effect. Innovation fosters adaptability and competitive advantage, while market orientation enhances customer focus and market responsiveness. The results underscore the importance of strategic leadership, innovative practices, and a market-driven approach in improving MSME performance. These insights provide practical recommendations for MSME stakeholders and policymakers to drive sustainable growth and competitiveness in the sector.